On some Hermite–Hadamard inequalities for fractional integrals and their applications - Hwang, S.-R.; Yeh, S.-Y.; Tseng, K.-L. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.5We establish some new extensions of Hermite\,--\,Hadamard inequality for fractional integrals and present several applications for the Beta function.